Antimicrobial activities of the crude extracts and electrospun nanofibers containing rhodomyrtus tomentosa (kemunting) roots - Zeyohanness, Senait Sileshi (2018)
Traditional medicinal plants can be used to treat chronic and infectious diseases. As a result, the practice of incorporating medicinal plant extracts into polymeric solutions to produce bioactive electrospun nanofibers is rising progressively. In this study Rhodomyrtus tomentosa roots were extracted with hexane, chloroform, ethyl acetate and methanol. Preliminary phytochemical analysis was done by using ultrahighperformance liquid chromatographyquadrupole time-off-light/mass spectrometry (UPLC QToF/MS) method and antimicrobial activity was evaluated against common human pathogenic microorganisms, two Gramnegative bacterial strains (Escherichia coli, Pseudomonas aeruginosa), two Grampositive bacterial strains (Bacillus subtilis, Enterococcus faecalis.) and one fungal strain (Aspergillus niger) by using disk diffusion method and zone of inhibition was determined. The extract with better activity, ethyl acetate extract (EAE), was incorporated with 10% Polyvinyl alcohol (PVA) (W/V) solution at different concentrations (0.25, 0.5, 1.5 and 2.5% W/V) and Ethyl acetate extract of Rhodomyrtus tomentosa roots incorporated in 10% PVA (RTE/PVA) nanofiber were fabricated using electrospinning process. Morphology of the extract loaded nanofibers were characterized using FESEM, FTIR and XRD spectrums. Antimicrobial activity of the electrospun nanofibers was evaluated using same procedures followed during the analysis of all extracts. Based on the UPLC QToF/MS analysis, it is confirmed that the root extract of Rhodomyrtus tomentosa contains flavonoids, tannins, xanthenes, phenols, glycosides, pheromones, chromones, triterpenes and pyranes. Ethyl acetate extract has been found to have good antibacterial activity with zone of inhibition ranging from 9.33 ± 0.21 mm to 13.67 ± 0.32 mm. Antimicrobial activity assay of ethyl acetate extract loaded PVA nanofiber was examined and showed good antibacterial activity. All the four solvent extracts of the plant material and the extract loaded PVA nanofiber have shown not to have any antifungal activity. Rhodomyrtone, known as a natural antibiotic, must contribute to the antibiotic activity against the above bacterial strains. Characterization of nanofibers indicates all weight ratios of the extract loaded PVA slution and the 10% PVA solution has made a nanofiber with a diameter in a range of 76.3 nm and 388.6 nm, respectively and the extracts were well incorporated with in the fibers.